Mutations in rrs, rpsL and gidB in streptomycin-resistant Mycobacterium tuberculosis isolates from Thailand. (March 2016) - Smittipat, Nat; Juthayothin, Tada; Billamas, Pamaree; Jaitrong, Sarinya; Rukseree, Kamolchanok; Dokladda, Kanchana; Chaiyasirinroje, Boonchai; Disratthakit, Areeya; Chaiprasert, Angkana; Mahasirimongkol, Surakameth; Yanai, Hideki; Yamada, Norio; et al.
Highlights: Mutations in rrs, rpsL and gidB and their association with strain type were studied. Mutations at codons 43 and 88 in rpsL were mostly associated with Beijing strains. Mutations in gidB were variable, some of which may be linked to resistance. Streptomycin (STR)-resistant Beijing strains mostly had mutations in both gidB and rrs (or rpsL ). STR-resistant non-Beijing strains mostly had only STR-conferring gidB mutation. Abstract: The objectives of this study were to characterise mutations in rrs, rpsL and gidB genes in Mycobacterium tuberculosis isolates from Thailand and to examine possible associations between mutations and strain genotypes. In total, 110 streptomycin (STR)-resistant M. tuberculosis isolates and 51 STR-susceptible isolates obtained from a sample collection in Thailand during 1999–2011 were sequenced for mutation analysis in rrs, rpsL and gidB . Genotypes of the isolates were identified using spoligotyping and large sequence polymorphisms. Mutations at codons 43 and 88 in rpsL represented 63.6% of the STR-resistant isolates and were mostly associated with Beijing strains. Mutations in rrs existed in 17.3% of the STR-resistant isolates; only 8.2% harboured resistance-associated mutations. Twenty-five different mutations were found in gidB, twelve of which are new. Eight gidB mutations were likely to contribute to STR resistance in ca. 14% of the resistant isolates; about one-half of the isolates also had a mutation in rrs or rpsL . Nearly all of the double mutants belonged to Beijing strains, whereas isolates carrying only STR-associated gidB mutation were non-Beijing strains. Three different alleles in gidB were also found, each specific to Beijing, East-African Indian and Euro-American lineages, respectively. Most of the STR-resistant isolates (80.9%) carried putative resistance-associated mutations in the analysed genes. Beijing strains were related not only to single resistance-associated mutations in rpsL or rrs but usually harboured a second mutation in gidB . Strains harbouring resistance-associated gidB mutations without rrs or rpsL mutations were more associated with non-Beijing isolates. Certain gidB mutations were also potential lineage markers.